2019
DOI: 10.1002/advs.201900023
|View full text |Cite
|
Sign up to set email alerts
|

Effective Delivery of Hypertrophic miRNA Inhibitor by Cholesterol‐Containing Nanocarriers for Preventing Pressure Overload Induced Cardiac Hypertrophy

Abstract: Persistent cardiac hypertrophy causes heart failure and sudden death. Gene therapy is a promising intervention for this disease, but is limited by the lack of effective delivery systems. Herein, it is reported that CHO‐PGEA (cholesterol (CHO)‐terminated ethanolamine‐aminated poly(glycidyl methacrylate)) can efficiently condense small RNAs into nanosystems for preventing cardiac hypertrophy. CHO‐PGEA contains two features: 1) lipophilic cholesterol groups enhance transfection efficiency in cardiomyocytes, 2) ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…As a result, miNPs treatment promoted angiogenesis in hypoxia, with low cytotoxicity in vitro, and improved cardiac function in vivo after 4 weeks. Furthermore, cardiac hypertrophy was improved in mice with aortic coarctation using cholesterol-terminated ethanolamine-aminated poly(glycidyl methacrylate) (CHO-PGEA) to deliver miR-182 inhibitor to cardiomyocytes with a high efficiency [132]. In this context, the delivery of miR-182 inhibitor resulted in the restoration the level of FOXO3, an anti-hypertrophic transcription factor, in the heart of affected animals, which in turn led to alleviation of cardiac hypertrophy, without side effects in other organs.…”
Section: Mirnas As Therapeutic Targets For Cardiac Diseasesmentioning
confidence: 99%
“…As a result, miNPs treatment promoted angiogenesis in hypoxia, with low cytotoxicity in vitro, and improved cardiac function in vivo after 4 weeks. Furthermore, cardiac hypertrophy was improved in mice with aortic coarctation using cholesterol-terminated ethanolamine-aminated poly(glycidyl methacrylate) (CHO-PGEA) to deliver miR-182 inhibitor to cardiomyocytes with a high efficiency [132]. In this context, the delivery of miR-182 inhibitor resulted in the restoration the level of FOXO3, an anti-hypertrophic transcription factor, in the heart of affected animals, which in turn led to alleviation of cardiac hypertrophy, without side effects in other organs.…”
Section: Mirnas As Therapeutic Targets For Cardiac Diseasesmentioning
confidence: 99%
“…Research into epigenetic mechanisms has achieved several notable breakthroughs, including dramatic improvements in the understanding of DNA methylation, histone modifications, and the role of noncoding RNA. The past decade has witnessed significant progress in RNA-based therapeutics for CVDs, [1][2][3] which pave the way toward precision medicine. Despite these important advances, factors such as instability, inadequate binding affinity, ease of delivery, immunogenicity, and off-target effects remain barriers to the widespread use of RNA-based therapeutics.…”
mentioning
confidence: 99%
“…Previously, we showed that cholesterol‐terminated ethanolamine‐aminated poly glycidyl methacrylate (CHO‐PEGA) nanoparticles efficiently deliver miRNA into CMs and heart tissues 22 . Employing the CHO‐PEGA carrier, we tested whether mir15a/mir16‐1 replenishment may rescue cardiac hypertrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that cholesterol-terminated ethanolamine-aminated poly glycidyl methacrylate (CHO-PEGA) nanoparticles efficiently deliver miRNA into CMs and heart tissues. 22 Employing the CHO-PEGA carrier, we tested whether mir15a/mir16-1 replenishment may rescue cardiac hypertrophy. CHO-PEGA was utilized to deliver mir15a/mir16-1 or negative control miRNA (mir NC) into cultured CMs after PE or recombinant IGF-1 (rIGF-1) treatment.…”
Section: Evidence Supporting Mir15a/mir16-1 As a Novel Therapeutic Tamentioning
confidence: 99%